Antibacterial Effect of Curcuma zedoaria Extract on Bacillus cereus and Staphylococcus epidermidis - Vidya Indriani; Linda Chiuman; Linda Leonando Wijaya; Gilbert Lister; Lexandria Grandis (Althea Medical Journal, 2020)
Background: White turmeric (Curcuma zedoaria), a plant used traditionally for medicine, is easily obtained at a relatively cheap price in Indonesia. White tumeric contains alkaloids, phenols, saponins, glycosides, steroids, terpenoids, and other compounds; and these compounds have shown antimicrobials, antifungal, anticancer, antiallergic, antioxidant, and analgesic effects. The aim of this study was to determine the antibacterial effect of white turmeric (Curcuma zedoaria) rhizome extract on the growth of Bacillus cereus and Staphylococcus epidermidis bacteria.Methods: This was an experimental study with a Post-test Only Control Group Design. It was carried out using the disc diffusion method with six treatments, consisting of negative control (aquadest), positive control (ciprofloxacin), and the extract of white turmeric rhizome with various concentrations. Kruskal Wallis test and one way ANOVA were used to analyze the data. The results showed a statistically significant value smaller than α (0.021 <0.05), and the One Way ANOVA test had a statistically significant value (p) less than α (0.000 <0.05).Results: The results of this research showed that the extract of white turmeric (Curcuma zedoaria) inhibited the growth of Bacillus cereus and Staphylococcus epidermidis bacteria at concentrations of 25%, 50%, 75%, and 100% as shown by the diameter inhibitory zone between 10-20 mm, compared to the positive control which had >20mm.Conclusions: Curcuma zedoaria has an antibacterial effect against Bacillus cereus and Staphylococcus epidermidis. Further study is needed, exploring the effectivity of white turmeric in the animal models.